Implementasi Metode Pembelajaran Pendidikan Agama Islam dalam Perspektif Konsep Rahmatan Lil Alamin - Hidayati; Aries Musnandar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
Character education in Indonesia is designed as a systematic effort to instill the behavioral values of students related to God Almighty, oneself, fellow human beings, the environment, and nationality. The purpose of this study was to determine and describe the implementation of the Rahmatan Lil Alamin (RLA) method in Islamic Religious Education (PAI) subjects for character development in Ketawang Gondanglegi Islamic Junior High School Malang. This research method is a qualitative research method with analysis in the form of descriptive narrative. Researchers act as the main instrument, namely planners, implementers, data collectors, analyzers, and reporting research results. The research was conducted through the implementation of lesson plans which included preliminary activities, core activities, and closing activities. The results obtained indicate that the Rahmatan Lil Alamin (RLA) method is able to strengthen the character education of students at Ketawang Gondanglegi Islamic Junior High School Malang who prioritize the nature of Humanism by applying the values of tasaamuh, islah, muwathanah, taadlul dan musyawarah. The components or indicators needed in learning when implementing the PAI learning method based on Rahmatan Lil Alamin values are more focused on student activity in the learning process or can be called caliph, learning that prioritizes ukhuwah and creates an atmosphere of learning environment that is baldatun tayyibatun warabbun ghofur. The implementation of the Rahmatan Lil Alamin (RLA) method is able to provide comfortable learning through student participation while still making teachers as role models and also facilitators of the learning process.